Perancangan Sistem Deteksi dan Pengenalan Rambu Peringatan Menggunakan Metode Template Matching - Thomas Oddy Chrisdwianto; Hurriyatul Fitriyah; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Digital image processing is useful for fixing image quality, so it we can recognize objects and provide the information we need. The first step of digital image processing is data acquisition. This process is to get the data that we need from the image. After that is the process of segmentation by grouping the image. The final step is the selection and extracting process, from this process we can analyze and display the information that contained in the image. One of the use of digital image processing is that it can be applied to the vehicle system as automatic driver assistant. With that system we can reduce the rate of accidents caused by human factors. Automatic driver assistant driver system can also help the driver for parking, auto pilot driving, detect traffic signs and assist the driver in performing the appropriate action. In this study, the detected traffic signs was a warning sign. Warning signs have an important role to warn the dangers that drivers must be faced. One of the simplest and easiest methods to recognize images is by using the Template Matching method. This method works by matching the images taken with the template. This method has a high success rate. The results of the program success rate test in recognizing the warning signals reached 88%.